Addressing the barriers to peritoneal dialysis—Visual appeal matters - Sam Stephens; Larissa Whale; Makenzie Kapales; Fatima Ayub; Morten O. Jensen; Manisha Singh (PLoS ONE, 2025)
Peritoneal dialysis (PD) is an effective renal replacement strategy for patients with end-stage renal disease utilizing the peritoneum as the filter and PD catheter as access. A survey of PD patients showed that some felt uncomfortable with the length of current catheters and would be interested to explore newer, shorter designs. We redesigned the transfer set and external portion of the catheter, addressing this barrier as a part of our multi-institutional design project led by a nephrologist from the University of Arkansas for Medical Sciences (UAMS) and an engineering design team from the biomedical engineering department at the University of Arkansas. Multiple designs were considered, including spiral, retractable, and collapsible bulbs, with an accordion-style mechanism being selected for prototyping. We created several prototypes, first by 3D printing as well as by silicone casting. Computational fluid analysis showed the design to be fully capable of delivering clinically relevant flows. The final design of our PD transfer set has a flexible accordion section that is 7 cm when extended and collapses to substantially shorten this length. We propose that the design can also be extended to the extra-abdominal section of the PD catheter.